2008
DOI: 10.4161/auto.6825
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and acute pancreatitis: A novel autophagy theory for trypsinogen activation

Abstract: K. Involvement of autophagy in trypsinogen activation within the pancreatic acinar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 13 publications
1
37
0
1
Order By: Relevance
“…In the cerulein-induced model of experimental pancreatitis, acinar cells develop cytoplasmic vacuoles that are autophagic in origin; these vesicles are involved in the degradation of zymogen granules, leading to the conversion of trypsinogen to trypsin, which accumulates within the acinar cell, triggering cellular self-digestion (23,27,50,58). Autophagy is required for this process, as trypsinogen activation is greatly reduced in mice that lack Atg5 specifically in acinar cells, and cerulein-induced acute pancreatitis does not develop in these mice (27).…”
Section: Discussionmentioning
confidence: 99%
“…In the cerulein-induced model of experimental pancreatitis, acinar cells develop cytoplasmic vacuoles that are autophagic in origin; these vesicles are involved in the degradation of zymogen granules, leading to the conversion of trypsinogen to trypsin, which accumulates within the acinar cell, triggering cellular self-digestion (23,27,50,58). Autophagy is required for this process, as trypsinogen activation is greatly reduced in mice that lack Atg5 specifically in acinar cells, and cerulein-induced acute pancreatitis does not develop in these mice (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports suggest that abnormalities in autophagic processing may play a role in the pathogenesis of pancreatitis (26). When the autophagy-related gene (Atg5) was genetically deleted in conditional knockout mice, trypsinogen activation was diminished and mice were protected against caerulein-induced experimental pancreatitis, suggesting that autophagic activation of trypsin may be required for the initiation of pancreatitis (9,27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mutations in the SPINK1 gene were associated to CP. A recent study also demonstrated the role of SPINK1 as a negative regulator of autophagy in mice-deficient SPINK3 (a mouse homologue gene of human SPINK1) (47).…”
Section: Disclosurementioning
confidence: 91%